Evolving Chineseness, Ethnicity and Business: The Making of the Ethnic Chinese as a ‘Market-Dominant Minority’ in Indonesia - HOON, Chang Yau (Institutional Knowledge at Singapore Management University, 2013)
The ethnic Chinese in Indonesia play a very significant role in the nation’s economy. Their dominance in the Indonesian economy is often seen as disproportionate to their numbers, as reflected in the popular assertion that “the Chinese constitute only 3.5 percent of the population but control 70 percent of Indonesia’s economy”. In the New York Times bestseller, World on Fire: How Exporting Free Market Democracy Breeds Ethnic Hatred and Global Instability, Amy Chua (2004) identified Chinese Indonesians as one of the “ market-dominant minorities” in the world. Her book highlights the double bind of free market democracy: it privileges certain ethnic minorities to dominate the market and accumulate wealth on the one hand, and also allows a frustrated indigenous majority to pit against the wealthy ethnic minority on the other. The book, which became phenomenally popular among the Chinese Indonesians in Indonesia, cited the May 1998 anti-Chinese riots in Indonesia as a prime example of its thesis. Although it does not offer any solution to their predicament, to many Chinese Indonesians, the book has provided a logical explanation to the vulnerable position of the Chinese minority in Indonesia.